Pre-urban Settlement: the Example of Skien - Myrvoll, Siri (Hikuin, 1998)
The position and development of early urban settlements, such as central places, meeting places, markets etc., depend to a large degree on an area’s topographical conditions as well as on its economic background and ready access to economic surplus and its power support. Various topographical factors - easy accessibility by land or water, good harbour facilities, a »comfortable«, sheltered and easily defensible site, good lines of communication between centre and hinterland and between centre and distribution area - will to a large extent determine the character of the settlement and its development within the local, national, or international distribution network. These factors are particularly important in a country with complicated topography, such as Norway, where settlements occur in clusters along the coastal fjords or inland valleys separated by often inaccessible mountainous terrain. In these countries inland communication is restricted, transport of goods took place by water, in barges on rivers or by ship along the coast. Indeed, waterways constituted the early inland road network, with fjords and sea routes as the main »highways«, tying together otherwise isolated communities and providing a link between countries.